Adverse obstetrical and neonatal outcomes in elective and medically indicated inductions of labor at term. (November 2013) - Baud, David; Rouiller, Sylvie; Hohlfeld, Patrick; Tolsa, Jean-Francois; Vial, Yvan
Abstract Objective: To compare the adverse neonatal and maternal outcomes after medically indicated and elective labor induction. Both induction groups were also compared to women with spontaneous onset of labor. Method: Retrospective cohort study of 13 971 women with live, cephalic singleton pregnancies who delivered at term (from 1997 to 2007). Adverse maternal and neonatal outcomes were compared between women who underwent an induction of labor in the presence and absence of standard medical indications. Results: Among 5090 patients with induced labor, 2059 (40.5%) underwent elective labor inductions, defined as inductions without any medical or obstetrical indication. Risks of cesarean or instrumental delivery, postpartum hemorrhage >500 ml, prolonged maternal hospitalization >6 days, Apgar<7 at 5 min of life, arterial umbilical cord pH<7.1, admission in neonatal intensive care unit (NICU) and prolonged NICU hospitalization >7 days were similar between nulliparous who underwent elective and medical labor induction. Similar results were obtained for multiparous. All the above mentioned risks, but the Apgar<7 at 5 min of life, were significantly increased after induction in comparison to spontaneous labor. Conclusion: Elective induction of labor carries similar obstetrical and neonatal risks as a medically indicated labor induction. Thus, elective induction of labor should be strongly discouraged.